KNOWLEDGE IMPROVEMENT OF SANDSTONE’S CRAFTSMEN IN A OCCUPATIONAL LUNG DISEASE PREVETION AT GAMPING VILLAGE - Nima Eka Nur Rahmania; Ellyza Setya Maryiantari; Wanda Aprilia Putri; Septika Alif Vira (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Health education in sandstone’s craftsmen at Gamping Village is one form of community service in the form of counseling to increasing understanding of the potential hazards and health impacts, especially on the lung function of craftsmen caused by exposure to sandstone dust that was inhaled during the production process. In addition to counseling, free health checks were also carried out, distribution of special respirable dust masks and simulations on how to use masks properly. The activity was carried out on June 17, 2022 at the Gamping Village, Tulungagung. The target of this activity was the sandstone craftsmen of Gamping Village. Before the activity was carried out, the activity preparation process was carried out for approximately 1 month starting from determining the extension theme to submitting permits to related parties. As a form of evaluation, the activity was attended by 32 participants consisting of sandstone craftsmen, village ministers and village officials. All participants participated in the activity with great enthusiasm. Counseling activities could run on time and smoothly.